Les enjeux des pratiques inclusives dans le domaine des loisirs. Du projet inclusif à la question des inscriptions sociales. Issue 2 (4th May 2021) - Marcellini, Anne
Abstract : Inclusive practices in the area of recreation for children or adults with disabilities are one dimension of the collective commitment to a future society that would ideally be transformed into an "inclusive" society. Such a society should be able to ensure access to common social practices for all its members, regardless of their singularities, differences, and disabilities. But transforming high-performance, competitive, individualistic societies into inclusive societies is a paradoxical challenge, as Charles Gardou has already pointed out. As such, this inclusive project, insufficiently worked on and understood, can lead to a reproduction, or even a worsening, of situations of disability. How can we ensure that access to shared leisure spaces and ordinary leisure time practices for children, adolescents, or adults with disabilities is not limited to a tolerated co-presence with other actors? Leisure, as unconstrained time and free space, is particularly conducive to the inclusive project. The study of the forms and dynamics of sustainable social inclusion of people with dis/abilities in different leisure sport environments reveals some of the essential characteristics of inclusive leisure configurations: self-determination, gift-giving and reciprocity, plurality of experiences, and free and non-timed time.